2019
DOI: 10.3390/ma12060939
|View full text |Cite
|
Sign up to set email alerts
|

Model Based on an Effective Material-Removal Rate to Evaluate Specific Energy Consumption in Grinding

Abstract: Grinding energy efficiency depends on the appropriate selection of cutting conditions, grinding wheel, and workpiece material. Additionally, the estimation of specific energy consumption is a good indicator to control the consumed energy during the grinding process. Consequently, this study develops a model of material-removal rate to estimate specific energy consumption based on the measurement of active power consumed in a plane surface grinding of C45K with different thermal treatments and AISI 304. This mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 32 publications
3
5
1
Order By: Relevance
“…10. The reduction of plowing energy with the material removal rate is in agreement with previous research on grinding [6,14]. The sliding power depends on the rotational speed of the cutting disc.…”
Section: Cutting Modelsupporting
confidence: 90%
See 1 more Smart Citation
“…10. The reduction of plowing energy with the material removal rate is in agreement with previous research on grinding [6,14]. The sliding power depends on the rotational speed of the cutting disc.…”
Section: Cutting Modelsupporting
confidence: 90%
“…High-energy deep grinding and cut-off operations take place predominantly in the material removal regime through a chip formation for ductile materials or through a crack formation for brittle materials. Nápoles et al [14] developed a material removal rate model to evaluate the specific energy consumption during industrial-scale grinding of C45K with different thermal treatments and AISI 304. It was demonstrated that the sliding energy was the main form of energy dissipation and decreased with an increase in the depth of the cut.…”
Section: Introductionmentioning
confidence: 99%
“…However, the introduction of this technology for the manufacture of components is faced with a number of difficulties. Grinding energy efficiency depends on the appropriate selection of cutting conditions, grinding wheel, workpiece material, and lubrication conditions [15,16]. There are difficulties with obtaining a repeatable result as it is difficult to achieve the assumed depth of hardening and to obtain the assumed hardness after grinding, which results in the necessity of applying the so-called softening grinding.…”
Section: Figurementioning
confidence: 99%
“…Researchers developed different models to analyse the dominance of particular energy component. For instance, Napoles et al [50] developed the material removal rate model to evaluate specific energy consumption during industrial scale grinding of C45K with different thermal treatments and AISI 304. They demonstrated that sliding energy is the main form of energy dissipation, and it decreases with increase of depth of cut.…”
Section: Dominance Of Specific Energy Components In Grinding Processesmentioning
confidence: 99%
“…The adopted model demonstrated the statistical accuracy to evaluate the specific energy consumption(SEC) with respect to material removal rate for the processes of grinding, milling, turning and injection moulding [64]. Recently, Napoles et al [50] adopted the same model for surface grinding to analyse the three energy components during industrial scale surface grinding.…”
Section: 3 Model Of Specific Energy Consumptionmentioning
confidence: 99%